2016
DOI: 10.1158/2326-6066.cir-15-0161
|View full text |Cite
|
Sign up to set email alerts
|

A Critical Role of miR-144 in Diffuse Large B-cell Lymphoma Proliferation and Invasion

Abstract: MicroRNAs are endogenous noncoding RNAs that play important roles in a wide variety of biologic processes such as apoptosis, development, aging, and tumorigenesis. The B-cell lymphoma 6 (BCL6) transcriptional repressor has emerged as a critical therapeutic target in diffuse large B-cell lymphomas (DLBCL), but the mechanisms regulating BCL6 are still unclear. In the current study, we screened the microRNA expression profiles in DLBCL specimens and cell lines by qRT-PCR and found that the expression of miR-144 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 35 publications
1
22
0
Order By: Relevance
“…Wang et al [48] first screened miRNA expression profiles in DLBCL tissues and cell lines and then performed target gene expression analysis to identify miRNAs that could be associated with lymphoma proliferation and invasion. MiR-144 was significantly decreased in samples and cell lines and was negatively correlated with BCL-6 expression.…”
Section: Functionally Significant Cellular Mirnas In Nhlmentioning
confidence: 99%
See 1 more Smart Citation
“…Wang et al [48] first screened miRNA expression profiles in DLBCL tissues and cell lines and then performed target gene expression analysis to identify miRNAs that could be associated with lymphoma proliferation and invasion. MiR-144 was significantly decreased in samples and cell lines and was negatively correlated with BCL-6 expression.…”
Section: Functionally Significant Cellular Mirnas In Nhlmentioning
confidence: 99%
“…MiR-144 has been identified as a tumour suppressor in osteosarcoma [49] and hepatocellular carcinoma [50]. The BCL family of proteins can have an anti-apoptotic function in haematological malignancies and hence miR-144 appears to be a viable biomarker and therapeutic target for lymphomagenesis [48]. It would be of interest to identify variants in the miR-144 and other BCL-6 -associated miRNAs′ precursor sequences, as well as variants in the BCL-6 target gene to perform genetic association analysis in DLBCL and also FL cases.…”
Section: Functionally Significant Cellular Mirnas In Nhlmentioning
confidence: 99%
“…miR-144 was originally identified to be an erythroid-specific miRNA, which is essential for the survival and maturation of the erythroid lineage (16,17). Ample studies have also reported that miR-144 acts as a tumor suppressor in different types of human cancer, including hepatocellular carcinoma (18), rectal cancer (19) and B-cell lymphoma (20 (21). However, the functional role of miR-144 in cervical cancer has remained to be elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…miR-144 expression was demonstrated to different effects from erythroid lineage to cancer (Dore et al, 2008). At the same time, miR-144 has been observed as a suppressor of cell invasion and metastasis including lymphoma (Wang et al, 2016), hepatocellular (Cao et al, 2014), bladder (Guo et al, 2013) and rectal cancer (Cai et al, 2015). miR-144 is known as a tumor suppressor which inhibits proliferation and promotes apoptosis of osteosarcoma cell lines (Ren et al, 2018).…”
Section: Discussionmentioning
confidence: 99%